Compliance with the Institutional Wage in Dualistic Models - Ana Paula Martins (Economics and Econometrics Research Institute (EERI), 2011)
This research extends simple two-sector models in order to inquire the impact of the extent of coverage or enforcement of minimum wage legislation in one of the sectors on the equilibrium outcome. Two versions of institutional wage avoidance are presented. They may be seen as representing different institutional detection rules: one working through worker complaint, the other through firm sampling inspection (and enforcement) by the legal system. Both cases are modelled as enlargements of two dualistic models: Harris-Todaro (the wage in the other sector is market determined) and Bhagwati-Hamada (the wage in the other sector is institutionally fixed and coverage is complete). Impact on population flows of changes in degree of coverage (compliance) is also confronted with the effect of a change in the institutional wage for each scenario.
Keywords: O15; O17; O18; R23; J38; J42; J61; J62; F22; K42; 330; Migration; Mobility; Minimum Wages; Segmented Labor Markets; Informal Sector; Regional Labor Markets; Dualistic Models; Coverage